Species composition, diversity and traditional uses of homegarden in Kumaun Himalaya, India - VIBHUTI, VIBHUTI; BARGALI, KIRAN; BARGALI, S S (The Indian Journal of Agricultural Sciences, 2019)
The aim of present study was to analyse the status, plant diversity and their utilization in homegardens of Kumaun Himalaya. After the recognizance survey, 12 villages were selected in Hill and Bhabhar regions and in each village10 homegardens were selected for detailed study. Out of 120 selected homegardens, 51 were large (>0.004 ha), 42 were medium (0.001-0.004 ha) and 27 were small (<0.001 ha). A total of 70 plant species belonging to 35 families were recorded. Herb density was maximum in large sized homegardens (479 ind./ha) followed by medium (317 ind./ha) and small sized homegardens (249 ind./ha). Tree density was maximum in large (825 ind./ha) as compared to medium (750 ind./ha) and small sized homegardens (317 ind./ha). Similarly, frequency of species occurrence increased with increasing homegarden size. Shannon-Weiner Index for both herbs (H’= 3.65) and trees (H’ = 2.51) were maximum in the large sized and minimum in small sized homegardens. Among the usable components, vegetable shared the half (50.78%) of the total plant diversity followed by fruits (22.57%), medicinal plants (18.03%), fodder (12.21%), fuel wood (7.35%) and ornamental species (1.43%) across all the homegardens in both the regions. Mangifera indica, Artocarpus integrifolia, Litchi chinensis, Bohermaria olerosa were the most frequent and dominant trees in all sized homegardens. This study suggested that large homegardens are more efficient than the small and medium sized homegardensand are ecologically, socially and economically diversified.